Ledipasvir-Sofosbuvir: Interferon-/Ribavirin-Free Regimen for Chronic Hepatitis C Virus Infection. (March 2015) - Smith, Michael A.; Chan, Juliana; Mohammad, Rima A.
Objectives: To review the pharmacology, efficacy, and safety of ledipasvir-sofosbuvir for the treatment of chronic hepatitis C virus (HCV).Data Sources: A literature search through clinicaltrials.gov, EMBASE, and PubMed was conducted (January 1966 to October 2014) using the terms ledipasvir, sofosbuvir, GS-5885, and GS-7977 . References from retrieved articles and abstracts presented at recent meetings were reviewed for any additional material. The prescribing information was also reviewed.Study Selection/Data Extraction: Phase 1, 2, and 3 human and animal studies describing the pharmacology, pharmacokinetics, efficacy, and safety of ledipasvir and sofosbuvir for HCV were identified.Data Synthesis: Ledipasvir-sofosbuvir, a fixed-dose combination (FDC) tablet inhibiting nonstructural (NS) 5A and 5B proteins, without peginterferon and ribavirin is indicated for adult patients with genotype 1 HCV infection who are treatment naïve or experienced, with or without cirrhosis. Pivotal trials (n = 1952) have demonstrated that once-daily administration of ledipasvir-sofosbuvir for 12 or 24 weeks is effective at achieving sustained virological response (SVR) rates (94%-99%) in treatment-naïve patients (12 weeks), treatment-experienced patients without cirrhosis (12 weeks), and treatment-experienced patients with cirrhosis (24 weeks). Treatment-naïve patients without cirrhosis and baseline viral levels of less than 6 million IU/mL may be considered for 8 weeks of treatment. The most common adverse drug events (ADEs) associated with ledipasvir-sofosbuvir include headache, fatigue, insomnia, nausea, and diarrhea.Conclusions: Ledipasvir-sofosbuvir is the first interferon- and ribavirin-free FDC agent that has SVR rates much greater than 94%, with minimal ADEs, for the treatment of chronic HCV genotype 1 in naïve and treatment-experienced patients.